ANALISIS KEANDALAN SISTEM JARINGAN DISTRIBUSI 20 KV DENGAN METODE FAILURE MODE EFFECT ANALYSIS DI PT PLN (PERSERO) ULP SUMBERPUCUNG PADA PENYULANG KALIPARE - Hakim, Lukmanul; Utomo, Teguh; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2024)
Electrical energy is generated from a plant and will be transmitted and distributed to be channeled to homes and consumed bycustomers. PT. PLN (Persero) or abbreviation of PT. Perusahaan Listrik Negara (Persero) is a state-owned company that movesand controls electricity starting from generation, transmission, and distribution to be distributed to homes and consumed bycustomers. ULP Sumberpucung or abbreviation of Sumberpucung Customer Service Unit is a sub-unit of UP3 Malang that isresponsible for customer service and overcoming electricity distribution problems with a smaller area. The calculation analysis ofthe 20 kV distribution network reliability system is a calculation analysis to find the values of SAIDI, SAIFI, and CAIDI. Thecalculation analysis carried out can use several methods, one of which is the FMEA (Failure Mode Effect Analysis) method. TheFMEA method is used to find the final results of SAIDI, SAIFI, and CAIDI values by identifying components that experienceinterference. The parameters used to determine the reliability index value with the manual calculation of the FMEA method include the failure rate of SPLN equipment, channel length, failure rate of each channel, repair time according to SPLN, repair rate, and the number of customers per distribution substation. The reliability index value can also be performed comparative analysis using ETAP 19.0.1 software. Analysis using ETAP software uses several parameters such as active failure rate, switching time, number of customers per load point, duration of component repair, and cable length. In addition, the results of the SAIDI value can be used to find the value of economic losses received by PLN in the event of a disturbance. The results of the analysis of manual calculations of the FMEA method and analysis on ETAP 19.0.1 software on the Kalipare Feeder at PT. PLN (Persero) ULPSumberpucung shows reliable results because the reliability index value is still below the provisions of SPLN No. 59 of 1985. Keywords: FMEA, ETAP, Interference Identification, Energy Not Supplied, Economic Value